Odpowiedź:
[tex]a)\ \ -1\frac{6}{7}+0,75=-1\frac{6}{7}+\frac{3}{4}=-1\frac{24}{28}+\frac{21}{28}=-1\frac{3}{28}\\\\\\b)\ \ -0,3-(-\frac{1}{3})=-\frac{3}{10}+\frac{1}{3}=-\frac{9}{30}+\frac{10}{30}=\frac{1}{30}\\\\\\c)\ \ -1\frac{3}{7}\cdot2,1=-\frac{\not10^1}{\not7_{1}}\cdot\frac{\not21^3}{\not10_{1}}=-3\\\\\\d)\ \ -1,2:(-\frac{4}{9})=\frac{12}{10}:\frac{4}{9}=\frac{\not6^3}{5}\cdot\frac{9}{\not4_{2}}=\frac{27}{10}=2\frac{7}{10}[/tex]
[tex]e)\ \ \frac{7-13}{2-5}+\frac{-2-10}{-2}=\frac{-6}{-3}+\frac{-12}{-2}=2+6=8[/tex]